Critical Conversations Among Critical Race Theory and Narrative Inquiry Educational Researchers - Gillies, Carmen; Stavrou, Stavros Georgios; Davis, Chelsea; Murphy, M. Shaun; Pinnegar, Stefinee (Journal of Critical Race Inquiry, 2026)
Using intimate scholarship (IS), we had conversations about the intersections of narrative inquiry (NI) and critical race theory (CRT) to better understand their value in our racial justice research. Building on Stavrou and Murphy’s (2021) five design elements, which they applied to CRT and anti-racist education, in this article we begin by identifying differences between NI and CRT and positing the use of counterstories to uncover potential intersections. Our article provides a critical review of recent studies based on NI and CRT. We articulate how this self-study of practice exemplifies IS and discuss counterstories from the basis of NI and CRT. Recognizing the limitations of the original 2021 NI and CRT design elements, we present revised elements and apply these to an analysis of a counterstory told by Shaun. We end by arguing that intertwining NI and CRT, when grounded in foundational theories, can uncover deeper understandings of experience and underexplored pathways to racial justice.